The Communication technologies to encourage innovative activities engagement in students - Soldatenko, Iryna (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The challenges of the new century have expanded the range of tasks universities are facing. In addition to traditional research and cultural tasks, the task of mastering the role of innovators not only in educational and research technologies - but also in cultivating socially responsible individuals and active citizens who are aware of global threats, able to anticipate risks, address social issues and develop the economy. The article presents the results of the author's sociology research on the following issues: how students of VN Karazin Kharkiv National University respond to global challenges, whether students are prepared to become part of a solution to global development challenges identified by the Government of Ukraine (based on UN Sustainable Development Goals) as a priority for the near future and what forms of innovative practices the students choose for this purpose. Attractive for students and young people, as an innovative practice enabling them to combine social activity and a startup, be independent of the state in the labor market and commence entrepreneurial activity in an exciting sector, is social entrepreneurship. Young people now feel congenial to the philosophy of social entrepreneurship, including many members of Generation Z? people aged 18 to 24, who care for the future of their country. According to the Diffusion of Innovation Theory by Everett Rogers, students belong to Early Majority of innovation adopters. For this group of innovators, it is important that information and communication programs should contain success stories and other evidence of the effectiveness of innovation, especially by opinion leaders of youth audiences. The article looks into the new communicative technologies of influence, which encourage students to innovate.